2009
DOI: 10.1108/14777260910979317
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of social capital as an indicator of community‐based initiatives (CBI) in the Islamic Republic of Iran

Abstract: The evaluation findings support the use of social capital indicators for investigating the impact and affectivity of CBI for health and development, and underlines the need for their consideration during implementation processes and further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…The difference in the functioning of the CHPS concepts in the two cases speaks to the presence of high social capital—at least for some of its proxies such as trust—as an indication of sufficient institutional performance. The findings in the present study are also consistent with the work of Sheikh et al 8. They noted from Iran that high levels of both cognitive and structural social capital (including associational affiliation, trust and citizenry activities) are associated with better operation and functioning of CBI that are meant to improve health-related quality of life and well-being.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The difference in the functioning of the CHPS concepts in the two cases speaks to the presence of high social capital—at least for some of its proxies such as trust—as an indication of sufficient institutional performance. The findings in the present study are also consistent with the work of Sheikh et al 8. They noted from Iran that high levels of both cognitive and structural social capital (including associational affiliation, trust and citizenry activities) are associated with better operation and functioning of CBI that are meant to improve health-related quality of life and well-being.…”
Section: Discussionsupporting
confidence: 92%
“…It was found that poor collaboration with communities and limited knowledge of community members partly accounted for failures in some HAZ 7. Sheikh et al 8 also note that in Iran, high levels of both cognitive and structural social capital (including associational affiliation, trust and citizenry activities) are associated with better operation and functioning of community-based initiatives (CBI) meant to improve health-related quality of life. It is thus high time to usher in further empirical evidence to ignite a rethink of strategies in sustaining the CHPS concept.…”
Section: Introductionmentioning
confidence: 99%
“…Other questions focused on household characteristics. Furthermore, the validated World Bank's social capital assessment tool on household social capital survey was used to collect household data on structural and cognitive aspects of social capital at both individual and collective levels[ 26 ]. Some of the questions on socio-demographic and household characteristics were adopted from the demographic and health survey questionnaire, which is well validated and widely used.…”
Section: Methodsmentioning
confidence: 99%
“…Research in many parts of Ghana have consistently registered that reliance on both close and distant social networks—including cognitive elements such as trust—lead to adoption and conflation of different forms of health practice and options without recourse to the referral system [ 31 , 32 ]. Developments in other sub-Saharan African countries [ 13 , 33 ] and other parts of the globe, especially low- and middle-income countries [ 34 ], have also shown similar patterns. However, none of the studies cited has examined the state of the referral policy from an explicit SC standpoint.…”
Section: Introductionmentioning
confidence: 94%